Borocarbonitrides as Metal‐Free Catalysts for the Hydrogen Evolution Reaction. Issue 13 (30th October 2018) - Rao, Chintamani Nagesa Ramachandra; Chhetri, Manjeet
Abstract: Hydrogen generation by water splitting is clearly a predominant and essential strategy to tackle the problems related to renewable energy. In this context, the discovery of proper catalysts for electrochemical and photochemical water splitting assumes great importance. There is also a serious intent to eliminate platinum and other noble metal catalysts. To replace Pt by a non‐metallic catalyst with desirable characteristics is a challenge. Borocarbonitrides, (Bx Cy Nz ) which constitutes a new class of 2D material, offer great promise as non‐metallic catalysts because of the easy tunability of bandgap, surface area, and other electronic properties with variation in composition. Recently, Bx Cy Nz composites with excellent electrochemical and photochemical hydrogen generation activities have been found, especially noteworthy being the observation that Bx Cy Nz with a carbon‐rich composition or its nanocomposites with MoS2 come close to Pt in electrocatalytic properties, showing equally good photochemical activity. Abstract : Borocarbonitrides, (Bx Cy Nz ) as a metal‐free electrocatalyst, exhibit superior activity in hydrogen generation. Carbon‐rich Bx Cy Nz contains more pyridinic and pyrollic nitrogens and a greater percentage of BC bonds with low proportion of BN domains and thus shows efficiency in the hydrogen evolution reaction by enhancing its conductivity. Excess of N substitution increases the electron population in the conduction bands to facilitate electrocatalysis.